Mortality following bone metastasis and skeletal-related events among men with prostate cancer: a population-based analysis of US Medicare beneficiaries, 1999–2006 - Sathiakumar, N; Delzell, E; Morrisey, M A; Falkson, C; Yong, M; Chia, V; Blackburn, J; Arora, T; Kilgore, M L (Prostate cancer and prostatic diseases, 2011)
Information on the impact of bone metastasis and skeletal-related events (SREs) on mortality among prostate cancer patients is limited. Using the linked Surveillance, Epidemiology and End Results (SEER)-Medicare database, we identified men aged 65 years or older diagnosed with prostate cancer between July 1 1999 and December 31 2005 and followed to determine deaths through December 31 2006. We classified subjects as having bone metastasis and SREs as indicated by Medicare claims. Using Cox regression, we estimated mortality hazards ratios (HR) among men with bone metastasis with or without SRE, compared with men without bone metastasis. Among 126 978 men with prostate cancer (median follow-up, 3.3 years), 9746 (7.7%) had bone metastasis at prostate cancer diagnosis (1.7%) or during follow-up (5.9%). SREs occurred in 4296 (44%) men with bone metastasis. HRs for risk of death were 6.6 (95% CI=6.4–6.9) and 10.2 (95% CI=9.8–10.7), respectively, for men with bone metastasis but no SRE and for men with bone metastasis plus SRE, compared with men without bone metastasis. Bone metastasis was associated with mortality among prostate cancer patients. This association appeared to be stronger for bone metastasis plus SRE than for bone metastasis without SRE.